A New Division of Schizophrenia Revealed Expanded Bilateral Brain Structural Abnormalities of the Association Cortices - Szendi, István; Szabó, Nikoletta; Domján, Nóra; Kincses, Zsigmond Tamás; Palkó, András; Vécsei, László; Racsmány, Mihály (Frontiers in Psychiatry, 2017)
The phenomenological and, consequently, pathophysiological heterogeneity of schizophrenia may be substantially decreased by determining aetiologically valid subgroups. In a cross-sectional study, we analysed the brain structural impairments of outpatients with schizophrenia using concurrent subgrouping methods, partly to enhance the extensity of exploration, and partly to estimate the validation of the divisions. High resolution T1 weighted MR images were obtained for 21 patients, and 13 healthy controls. Localized grey matter volumetric deficits were defined with optimized voxel-based morphometry. Employing two concurrent methods (i.e. the widely-known deficit-nondeficit division vs. the neurocognitive clusters we identified earlier) the patient group was iteratively divided into two subgroups, and their volumetric peculiarities were compared with one another and with healthy controls. Our division revealed more significant differences demonstrating bilateral brain structural deficits, which affected the association cortices, primarily the heteromodal fields and partly the unimodal fields. This is the first study that showed that abnormalities of the association cortices can be bihemispherial and expanded in schizophrenia, even in the cases of outpatients living integrated in society. Our result suggests that the extended association cortex abnormalities could constitute substantial and determining neurological substrates in the phenomenology and aetiopathogenesis of schizophrenia, at least in a subgroup of patients with more unfavorable neurocognitive characteristics.